Highly Selective and Sensitive Colorimetric and Fluorescent Chemosensors for Rapid Detection of Cyanide Anions in Aqueous Medium: Investigation on Supramolecular Recognition of Tweezer‑shaped Salophenes - Darabi, Hossein Reza; Nazarian, Ramo; Alizadeh, Sepideh; Aghapoor, Kioumars; Ebadinia, Leila (Journal of fluorescence, 2021)
Three tweezer‑shaped salophenes having catechols ( 1 ), phenols ( 2 ) and anisoles ( 3 ) units in conjunction to the dipodal Schiff bases have been applied for the optical sensing of cyanide (CN¯) ions in CH 3 CN-H 2 O (7:3) as solvent of choice. Among them, compounds 1 and 2 recognized CN¯, relying on distinct color and spectral changes. They are easy-to-use probes that exhibit extremely high sensitivity (limit of detection = 1–10 nM), rapid response (5 s) and excellent selectivity. Moreover, the visual detection and concentration determination of CN¯ by solution test kits of both sensors are the advantages for the practical applications. Based on the fluorescence and NMR spectroscopy, as well as the OH¯ and reversibility experiments, the explicit effect of hydroxyl groups on sensing and as well the different recognition of 1 and 2 toward CN¯ ions was proved. While probe 1 senses CN¯ via deprotonation, probe 2 recognizes it through an intramolecular aldimine condensation cyclization, leading to formation of anions of dihydroxyquinoxaline 4 . This chemodosimetry is being reported for the first time in a Schiff’s base. Furthermore, the similarity of fluorescence and NMR responses of 2 and 4 toward CN¯ supports the proposed process.